Eleventh Periodic Monitoring Report on The Status of Management Implementation Plans In Response To Board-Endorsed IEO Recommendations. - International Monetary Fund. Office of Internal Audit (Washington, D.C. : International Monetary Fund, 2021)
The Eleventh Periodic Monitoring Report (PMR) on the Status of Management Implementation Plans (MIPs) in Response to Board-Endorsed Independent Evaluation Office (IEO) Recommendations assessed the progress made over the past 18 months on 72 actions contained in 10 MIPs. Significant progress has been made with the implementation of management actions, despite challenges that have arisen from the ongoing COVID-19 pandemic. Overall, 29 of the 72 actions for which implementation progress is assessed in the Eleventh PMR were deemed to have been satisfactorily implemented, while 35 remain open, and eight actions are being reformulated in line with the Board-approved triage framework for long-standing open actions. Despite the effect of reprioritization to make space for the urgent needs of the membership resulting from the pandemic, the pace of implementation observed in the Eleventh PMR, with the 29 actions closed, significantly exceeds the previous trend of about 15 implemented actions per year. Of the 35 open actions, 16 are more than one year past their implementation due dates. The reprioritization of activities owing to the COVID-19 pandemic and resource constraints on account of several years of flat budgets led to delays in the implementation of several actions, partly because of the postponement of important reviews.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Political Economy